Improvement on Document Control Review System in Document Control Section, at PT. ASIKA, Cikarang - Religia Isna Putranti (President University, 2016)
PT. ASIKA Indonesia is a big manufacturing toy company in Indonesia. Many problems occur in PT. ASIKA Indonesia. The obstacle that may occur such as about the product quality, the technological system of the company or the documentation system of the company. In this section, the obstacle that occurs in PT. ASIKA Indonesia is the double counted of Standard Operating Procedure (SOP) and some of the documents have not been registered yet even those documents are legal documents. It has the impact on the quality management system of the company. It will give impact when the company needs to review and audit all the legal documents of PT. ASIKA Indonesia. Thus, it is needed to conduct the research on document control. The procedures and the applicable documents such as form will be reviewed. The analysis is performed on a list of Standard Operational Procedures (SOP)s and forms. Pareto diagram is also constructed with pie chart and pivot table as a tool. After conduct the analysis, it will make the user ease to find the procedure and the related document in the documentation system without double counted.